Pengaruh Penerapan Model Pembelajaran Discovery Learning Terhadap Kemampuan Hots (High Order Thinkng Skill) Siswa Kelas X MIPA SMAN 3 Padang - INDRA KURNIAWAN REZKI (Departemen Matematika, 2019)
Globalization has had an impact on various aspects of life, except education. The study aims to examine the effect of the application of the Discovery Learning learning model on the ability of High Order Thinking Skills (HOTS) as a new challenge for students in the 21st century. The final test of the study was tested based on three levels of questions based on Bloom's taxonomy namely analyzing, evaluating, and creating. In this study the hypothesis test compares the t-value with α (the established real level is 0.05. H0 is rejected > α. Based on the results of the hypothesis test obtained means that <α so that it can be concluded that H0 rejected or H1 accepted The results showed that the ability of HOTS students of class X MIPA SMAN 3 Padang who used the Discovery Learning learning model was better than students who used conventional learning models. Keywords — Learning models, Discovery Learning, High Order Thinking Skill (HOTS).